Embelin Restores Carbapenem Efficacy against NDM-1-Positive Pathogens - Ning, Nian-Zhi; Liu, Xiong; Chen, Fanghong; Zhou, Peng; Hu, Lihong; Huang, Jian; Li, Zhan; Huang, Jie; Li, Tao; Wang, Hui (Frontiers in Microbiology, 2018)
The emergence and spread of carbapenemase in Gram-negative pathogens poses an enormous threat to global public health. New Delhi metallo-β-lactamase-1 (NDM-1) inactivates nearly every class of β-lactam antibiotics, including carbapenem; however, there is no clinically useful NDM-1 inhibitor. Embelin,an important ingredient in traditional herbal medicine, has anti-tumor effects. The current study is the first to discover and examine the inhibitory activity of embelin against β-lactamase NDM-1. The IC50 of embelin was 2.1±0.2 μM when tested against NDM-1 carbapenemase. Most regions of the embelin molecule were buried within NDM-1’s active site, and the hydroxyl group of embelin interacted directly with the metal ion Zn2+, as shown by molecular dynamic simulation. Systematic analysis of the antibacterial activities of embelin and antibiotics demonstrated that embelin restored meropenem activity against a panel of NDM-positive pathogens, such as Escherichia coli, Klebsiella pneumoniae and Acinetobacter baumannii. Based on these results, embelin could be a promising carbapenem adjuvant candidate against NDM-1-producing bacterial strains.